POLITIK DAN âTEATER RITUALâ DI BALI - Suryawan, I Ngurah (IAIN Walisongo Semarang, 2012)
Abstract Â The relation between ritual and socio-political environment should become a deep eflection. Rituals which take place in order for salvation, harmony, and natural balance instead generate the ambigue and ironic situation. Rituals had been going on amazingly but the social as well as natural disasters seems go on continually. In Bali, religious rituals that formerly guarded by mantra-mantra (spiritual wordings) recently enstead by a group of Pecalang (tradition guardian in Bali) and metal detector (at the time of Pamarisudha Karipubhaya Bali Blast of 2002 and 2005). Nowadays Balinese are eager to perform rituals spectacularly. But instead, Bali now is struck by continous disaster, not only the disaster came from external sources but also the internal ones. Â *** Hubungan antara ritual dengan lingkungan sosial politik harus menjadi bahan renungan yang dalam. Ritual yang dilakukan untuk tujuan keselamatan, harmoni, dan keseimbangan alam bahkan menimbulkan kondisi ambigue dan ironis. Ritual berjalan secara mengesankan namun bencana sosial maupun bencana alam terus menerus terjadi. Di Bali, ritual agama yang sebelumnya diwarnai mantra-mantra kini diisi oleh Pecalang (pengawal tradisi Bali) dan metal detector (pada saat Pamarisudha Kariphaya Bom Bali 2002 dan 2005). Kini orang Bali cenderung melaksanakan ritual secara spektakuler. Akan tetapi Bali seringkali didera bencana, baik bencana yang berasal dari dalam maupun luar. Â Keywords: ritual, disaster, mantra, pecalang, harmoni